2000
DOI: 10.1021/bi0014406
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Lipid-Free Structure and Stability of Apolipoprotein A-I by Mutation

Abstract: To probe the secondary structure of the C-terminus (residues 165-243) of lipid-free human apolipoprotein A-I (apoA-I) and its role in protein stability, recombinant wild-type and seven site-specific mutants have been produced in C127 cells, purified, and studied by circular dichroism and fluorescence spectroscopy. A double substitution (G185P, G186P) increases the protein stability without altering the secondary structure, suggesting that G185 and G186 are located in a loop/disordered region. A triple substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
76
3
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(93 citation statements)
references
References 47 publications
10
76
3
3
Order By: Relevance
“…(30). A mutation G185P/G186P located in the Cterminal part of apoA-I affects fluorescence of tryptophans located in the N-terminal half of apoA-I, which suggests a close proximity of the N-and C-termini of apoA-I and their interaction with each other in solution (29). Substitutions L222K/F225K/F229K (29) and E125K/E128K/K133E/E139K (30) stabilize lipid-free apoA-I and increase its α-helical content, while substitutions V156K/A158E (45) and E110A/E111A (12) destabilize the protein and result in a loss of helical structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(30). A mutation G185P/G186P located in the Cterminal part of apoA-I affects fluorescence of tryptophans located in the N-terminal half of apoA-I, which suggests a close proximity of the N-and C-termini of apoA-I and their interaction with each other in solution (29). Substitutions L222K/F225K/F229K (29) and E125K/E128K/K133E/E139K (30) stabilize lipid-free apoA-I and increase its α-helical content, while substitutions V156K/A158E (45) and E110A/E111A (12) destabilize the protein and result in a loss of helical structure.…”
Section: Discussionmentioning
confidence: 99%
“…Far-UV CD spectra were recorded as described previously (29,30). For each protein, spectra were recorded at several protein concentrations within the indicated range and then normalized to molar residue ellipticity.…”
Section: Circular Dichroism Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…A continuous helix repeat assignment describes 10 tandemly repeated helices punctuated mainly by prolines. However, although this continuous helical model is the most widely used one, assignment of the precise secondary structural distribution throughout the apoA-I sequence is far from agreement by different approaches [11,[15][16][17][18][19][20][21][22] Thus, studies of peptides [15,[23][24][25] that model different regions of apoA-I can provide important information on the roles of specific residues and segments, and their interactions in the structure and stability of the parent apolipoprotein. Analysis of the consensus sequences of the A and B repeat derived from the sequences of multiple exchangeable apolipoproteins [7], together with studies of 44-residue consensus sequence peptides, showed ~ 90% and 5 0% α-helical contents for peptides with ABAB [26] and ABBA [27] sequence ordering respectively.…”
mentioning
confidence: 99%